EFFECT OF GIVING A NATURAL GUARD IN DRINKING WATER GIVEN DAILY ON AVIAN INFLUENZA ANTIBODY TITER OF LAYING HENS - Deysi Arviani Dewi Arnaya; Anak Agung Gde Jayawardhita; Tri Komala Sari (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Laying hens are a type of livestock that is widely cultivated in almost all regions in Indonesia. However, laying hens are also susceptible to many diseases caused by bacteria and viruses. Avian Influenza (AI) virus is one example of a virus that can harm farmers because it can cause high mortality rates. The presence of disease cases caused by viruses can be prevented by increasing the antibody titer in laying hens. The purpose of this study was to determine the effect of Natural Guard in drinking water on increasing AI antibody titer in laying hens. This study was experimental in nature using 24 samples. Laying hens were divided into four groups: P0 (control, no treatment), P1 (0.1 ml/L), P2 (0.2 ml/L), and P3 (0.3 ml/L) of Natural Guard given daily for 30 days. Antibody titers were measured using the hemagglutination inhibition (HI) test. The results of the analysis showed that the highest average antibody titer was found in the P1 group, but the ANOVA test showed no significant difference between treatment groups (p>0.05). Thus, the administration of Natural Guard had no significant effect on increasing AI antibody titer in laying hens. Future research is recommended to use a higher dose and appropriate sampling time during the peak of antibody formation.